Stabilization of Soil Using Eggshell Powder as a Partial Replacement for Lime: A Sustainable Approach - Adnan; Jawad, Ahmad; Raza, Hassam; Alam, Dawood Shah (Jurnal Civil Engineering Study, 2024)
This study assesses the effectiveness of lime in stabilizing soil and focus on the prospects of using eggshell powder as an economic and environmentally friendly alternative to lime. To ascertain the impact of different degrees of eggshell powder, particular at 0.5 g, 1g, 1.5g and 2g equivalent to 0.5%, 1%, 1.5% and 2% the weight of the soil respectively; and to replace up to 50% of the lime within the stabilization handle. This study proves that all treated tests shown relatively better result than untreated soil, that must satisfactory to ensure the stabilization strategy. Without a doubt, when lime is substituted with 25% of eggshell powder in the concrete formulation where favorable strength characteristics were obtained, it established that this level of substitution may well be carried out feasibly in practical use. This ponder supports the sensible treatment of accumulating eggshell powder to advance soil compactness and recommends discovering more deliberately wakeful development rehearses through utilizing waste products. The research finds reveal ways in which cost can be reduced and the soil natural appearance lost with traditional methods of soil stabilization can be minimized.